2014
DOI: 10.12980/apjtb.4.2014c179
|View full text |Cite
|
Sign up to set email alerts
|

A note on treatment of hyperthermia in crossbred cattle

Abstract: The findings of this study substantiate that subcutaneous administration of three doses of iodized oil given at 24 h interval is effective in decreasing rectal temperature of hyperthermic cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Chandra et al [22] reported that RT of KF remained significantly high compared to Sahiwal and Tharparkar cattle during different seasons and the magnitude of increase in RT was higher in KF than Sahiwal and Tharparkar during summer season. Randhawa et al [23] reported that the temperature humidity index (THI) describes the effect of environment on animal's ability to dissipate heat. During drought, the ambient temperature and RH frequently exceed the critical comfort level of THI (72), resulting in elevated body temperature and panting.…”
Section: Physiological Responsesmentioning
confidence: 99%
“…Chandra et al [22] reported that RT of KF remained significantly high compared to Sahiwal and Tharparkar cattle during different seasons and the magnitude of increase in RT was higher in KF than Sahiwal and Tharparkar during summer season. Randhawa et al [23] reported that the temperature humidity index (THI) describes the effect of environment on animal's ability to dissipate heat. During drought, the ambient temperature and RH frequently exceed the critical comfort level of THI (72), resulting in elevated body temperature and panting.…”
Section: Physiological Responsesmentioning
confidence: 99%
“…This fact makes the air temperature in the afternoon to be the origin of a high rectal temperature in the tropics, especially in the summer. Therefore, it can be used to assess the thermal stress level of animals during this period as rectal temperature measurement is often used as an index of physiological adaptability to warm environments because its increase shows that mechanisms of heat release became inefficient (Randhawa, Chhabra, Randhawa, Zahid, & Dhaliwa, 2014). The fact that animals showed a normal RT despite the high BGTHI value shows their efficient mechanisms to maintain homeothermia and that water salinity levels do not affect this balance.…”
Section: Discussionmentioning
confidence: 99%
“…Continental European breeds, such as Charolais, were selected based on their aptitude to produce meat and traction, resulting in animals with greater muscling than other European breeds, especially of British origin, which were selected based on quantitative and qualitative carcass and meat traits (Gregory and Cundiff, 1980). In Zebu breeds, such as Nellore, due to their tolerance to warm climates, natural selection resulted in animals with a thinner (Randhawa et al, 2014), lighter structure, with low muscle and bone mass, and better fat deposition than the Charolais breed (Restle et al, 2002).…”
Section: Effects Of Genetic Groups Within Mating Systems (Purebred and Crossbred)mentioning
confidence: 99%